Integrative proteomics reveals mitochondrial and immune signatures of MLH1 exon 13 deletion in Lynch syndrome–associated colorectal cancer - Chang, Chen; Cao, Yue; Zhang, Bin; Chen, Jingli; Chen, Lin; Li, Wensheng; Wang, Guorong (Frontiers in Molecular Biosciences, 2025)
BackgroundLynch syndrome is an inherited cancer predisposition caused by pathogenic variants in mismatch repair (MMR) genes. Large genomic rearrangements (LGRs) in MLH1 are often underestimated due to detection challenges. Functional analyses of specific variants such as MLH1 exon 13 deletion (MLH1-EX13 Del) remain scarce.MethodsA three-generation Chinese family with Lynch syndrome was investigated. Targeted next-generation sequencing identified MLH1-EX13 Del in the proband, which was validated by qPCR in family members. Cancer patients underwent MMR immunohistochemistry (IHC) and microsatellite instability (MSI) testing. Data-independent acquisition proteomics was performed on four paired tumor and adjacent tissues, followed by Gene Ontology and KEGG enrichment analyses.ResultsSix malignant tumors were diagnosed in the family. All tested carriers harbored MLH1-EX13 Del. IHC showed loss of MLH1 and PMS2, occasionally with focal MLH1 positivity or concurrent MSH2 loss. All tumors tested were MSI-H. Proteomics revealed systemic downregulation of oxidative phosphorylation across mitochondrial respiratory complexes, whereas ribosome biogenesis proteins were upregulated, indicating enhanced protein synthesis. Immune pathway analysis revealed activation of neutrophil-mediated immunity and upregulation of inflammatory markers (S100A8/A9, MPO, ELANE), consistent with an inflamed tumor phenotype.ConclusionThis study provides the first proteomic evidence linking MLH1-EX13 Del to suppressed mitochondrial metabolism and immune activation. These findings highlight metabolic vulnerability and an inflammatory microenvironment as potential therapeutic targets, offering new insights into Lynch syndrome-associated colorectal cancer.